Identification of carotenoids from the extremely halophilic archaeon Haloarcula japonica - Yatsunami, Rie; Ando, Ai; Yang, Ying; Takaichi, Shinichi; Kohno, Masahiro; Matsumura, Yuriko; Ikeda, Hiroshi; Fukui, Toshiaki; Nakasone, Kaoru; Fujita, Nobuyuki; Sekine, Mitsuo; Takashina, Tomonori; et al. (Frontiers in Microbiology, 2014)
The carotenoids produced by extremely halophilic archaeon Haloarcula japonica were extracted and identified by their chemical, chromatographic, and spectroscopic characteristics (UV-Vis and mass spectrometry). The composition (mol%) was 68.1% bacterioruberin, 22.5% monoanhydrobacterioruberin, 9.3% bisanhydrobacterioruberin, < 0.1% isopentenyldehydrorhodopin, and trace amounts of lycopene and phytoene. The in vitro scavenging capacity of a carotenoid, bacterioruberin, extracted from Ha. japonica cells against 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals was evaluated. The antioxidant capacity of bacterioruberin was much higher than that of β-carotene.